Pengaruh Kepuasan Kerja, Job Insecurity, dan Beban Kerja terhadap Turnover Intention Karyawan Industri Pengolahan Susu Kambing Etta Indotama - Juleiqa, Siti; Indarto, Muhammad Roni (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
This study aims to analyze the influence of job satisfaction, job insecurity, and workload on turnover intention of employees in the Etta Indotama goat milk processing industry. The independent variables in this research are job satisfaction, job insecurity, and workload while the dependent variable is turnover intention. The data collection methodology for this research involved the use of a questionnaire distributed via Google Forms. The population targeted for this research is all production employees in the Etta Indotama environment. Sampling used non-probability sampling with saturated sampling technique. The total sample was 170 respondents. The tests used in testing research instruments and questionnaire data include validity tests, reliability tests, normality tests, multicollinearity tests, and heteroscedasticity tests. The data analysis techniques used are multiple linear regression analysis, partial t test, and coefficient of determination. The results of this research show that job satisfaction has a negative effect on turnover intention of employees in the Etta Indotama goat milk processing industry. Job insecurity has a positive effect on employee turnover intention in the Etta Indotama goat milk processing industry. Workload also has a positive influence on worker turnover intention at the Etta Indotama milk factory